Women’s Leadership in Islamic Law: Between Normative Foundations and Contemporary Realities - Chika Praska Anggraini; Darul Akbar; M. Fijar Ishlahul Ummah (NUSANTARA: Journal Of Law Studies, 2024)
This article examines the concept of women’s leadership within the framework of Islamic law, with a focus on the intersection between normative foundations and contemporary realities. Historically, discussions on imāmah al-mar’ah (female leadership) were dominated by classical jurists, whose interpretations often reflected the patriarchal structures and socio-political contexts of their time. However, with the evolution of modern Muslim societies and the rise of gender justice discourse, these interpretations require renewed contextualization. Using a qualitative-descriptive method through library research and comparative textual analysis, this study examines the arguments of prominent classical scholars such as al-Māwardī, Ibn Ḥazm, and al-Ghazālī, alongside contemporary reformists including Fazlur Rahman and Amina Wadud. The analysis employs hermeneutical reasoning and the maqāṣid al-sharī‘ah framework to explore the flexibility of Islamic legal interpretation. The findings reveal three key points. First, classical prohibitions on women’s leadership were more sociological than theological, rooted in historical contexts rather than immutable divine injunctions. Second, when assessed through the lens of maqāṣid al-sharī‘ah,women’s leadership aligns with the higher objectives of justice (al-‘adl), benefit (maṣlaḥah), and human dignity. Third, contemporary interpretations suggest a shift from gender-based exclusion to competence- and morality-based inclusion, enabling greater participation by women in political, social, and religious leadership. The study’s academic contribution lies in proposing a maqāṣid-based reinterpretation model that bridges textual orthodoxy with modern gender realities. This framework enriches Islamic legal scholarship by demonstrating that Shariah is not static butadaptive, capable of supporting egalitarian leadership principles that respond to the ethical and social demands of the modern era.